2013
DOI: 10.1037/a0032663
|View full text |Cite
|
Sign up to set email alerts
|

Teams as innovative systems: Multilevel motivational antecedents of innovation in R&D teams.

Abstract: Integrating theories of proactive motivation, team innovation climate, and motivation in teams, we developed and tested a multilevel model of motivators of innovative performance in teams. Analyses of multisource data from 428 members of 95 research and development (R&D) teams across 33 Chinese firms indicated that team-level support for innovation climate captured motivational mechanisms that mediated between transformational leadership and team innovative performance, whereas members' motivational states (ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
215
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(234 citation statements)
references
References 59 publications
13
215
1
5
Order By: Relevance
“…Employees with highly creative self-efficacy behave in a self-starting manner rather than 'do[ing] things by the book' (Raub & Liao, 2012, p. 654). They are more proactive in terms of implementing creative ideas and trying new methods (Chen, Farh, Campbell-Bush, Wu, & Wu, 2013;Raub & Liao, 2012). Finally, Ryan and Deci (2000) indicated that employees engage intrinsically in activities when they feel efficacious with respect to those activities.…”
Section: Service Innovation Behaviormentioning
confidence: 96%
“…Employees with highly creative self-efficacy behave in a self-starting manner rather than 'do[ing] things by the book' (Raub & Liao, 2012, p. 654). They are more proactive in terms of implementing creative ideas and trying new methods (Chen, Farh, Campbell-Bush, Wu, & Wu, 2013;Raub & Liao, 2012). Finally, Ryan and Deci (2000) indicated that employees engage intrinsically in activities when they feel efficacious with respect to those activities.…”
Section: Service Innovation Behaviormentioning
confidence: 96%
“…Empirically, while there is consistent evidence that shared perceptions of innovation-supportive climate affect motivation factors related to employee engagement in innovative behaviours (e.g. Chen et al 2013), research has shown that individual-level perceptions of supportive team and organizational environments can also have a significant impact on change-oriented regulatory processes (e.g. Choi 2004;Yuan and Woodman 2010).…”
Section: Confirmatory Factor Analysis and Assessment Of Common Methodmentioning
confidence: 98%
“…Such dispositional attributes have been posited as promoters of both individual and team innovation (Chen, Farh, Campbell‐Bush, Wu, & Wu, ; Crant, ). In accordance, Grant and Ashford () presented a proactivity process perspective, arguing that proactive individuals anticipate future events and are mindful of the effects of their actions.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%